Effects of combined cyclosporin and azithromycin treatment on human mononuclear cells under lipopolysaccharide challenge - Alotaibi, Norah; Alesawy, Aminah; Alalshaikh, Marwa; Aljofi, Faisal E.; Aldossary, Nada; Alzahrani, Nada; Omar, Omar; Madi, Marwa (Frontiers in Oral Health, 2025)
ObjectiveTo evaluate the combined effects of azithromycin and varying concentrations of cyclosporin on peripheral blood mononuclear cells (PBMCs) under lipopolysaccharide (LPS) stimulation.Materials and methodsPBMCs were isolated from four healthy donors and treated with cyclosporin at concentrations of (50, 200, and 1,000 ng/ml) either alone or in combination with azithromycin (0.4 µg/ml), with and without 100 ng ml LPS derived from Porphyromonas gingivalis. Total cell count, cell viability, and lactate dehydrogenase (LDH) activity were assessed at day 1 and 3. While the inflammatory mediators, including IL-6, IL-1β, IL-18, and IgA levels were assessed by ELISA at day 3. Statistical analysis included two-way ANOVA to analyze the effects of the drugs and the presence of LPS (the two independent variables), followed by Tukey's HSD post-hoc test. Multiple linear regression models evaluating treatment effects, LPS exposure, and time points, with assessment of two-way interactions. Models were adjusted for relevant covariates and verified for statistical assumptions, with significance set at p < 0.05.ResultsLower cyclosporin concentrations (50 and 200 ng/ml) combined with azithromycin maintained higher cell counts and showed reduced cytotoxicity compared to 1,000 ng/ml under LPS exposure. The 200 ng/ml cyclosporin-azithromycin combination demonstrated optimal results, reducing IL-6 and IL-1β levels while maintaining cell viability. Higher concentrations elevated IgA levels, particularly with LPS stimulation, suggesting enhanced immune response modulation.ConclusionThe combination of azithromycin with moderate cyclosporin concentrations (200 ng/ml) provides optimal immunomodulatory effects while maintaining cell viability. Higher cyclosporin doses (1,000 ng/ml) showed increased cytotoxicity despite enhanced immunomodulation.